Seeking sustainable pathways for fostering agricultural transformation in peninsular India - Anantha, K.H.; Garg, K.K.; Petrie, C.A; Dixit, S. (IOP Publishing, 2021)
Sizable populations in developing countries in Asia and Africa live in dryland ecosystems, and agriculture in these areas faces major challenges including water scarcity, land degradation, poor infrastructure and insufficient access to markets. Natural resource management (NRM) interventions offer an important path to sustainable agricultural practices through increasing resource use efficiency, but true efficacy will only be achievable if these initiatives can be scaled up. This paper explores the impact of farm-scale NRM interventions undertaken in the state of Karnataka, India, between 2005 and 2020. NRM technologies such as soil health management, resource use efficiency and improved crop cultivars were demonstrated in more than 50 000 farmers' fields. Participatory demonstrations and capacity building initiatives were effectively used to co-create innovations for rapid and wide dissemination, and NRM practices involving the soil-nutrient-crop-water continuum were the subject of large-scale demonstrations. The demonstration fields were divided into treated and control fields, and efforts were made to measure cost of cultivation, irrigation application and crop yield. The soil health management interventions helped to enhance crop yield by 10%–60% over the control plots. Technologies specific to resource conservation have helped to conserve soil moisture, reduce irrigation requirement by 50–300 mm and reduce the cost of cultivation by US$ 150 ha−1. Improved cereal, pulse and oil seed cultivars increased crop yield minimum by 15%. Although these results have a large variability, they consistently showed the effectiveness of integrating NRM practices with crop demonstrations. These results are ideal for sensitizing stakeholders and policymakers to the benefits of adopting science-based approaches to NRM interventions in order to bridge yield gaps and address land degradation, food insecurity and poverty in dryland regions in South Asia and globally.